Impact of fluorescent silicon nanoparticles on circulating hemolymph and hematopoiesis in an invertebrate model organism. (September 2016) - Xing, Rui; Li, Kai-Le; Zhou, Yan-Feng; Su, Yuan-Yuan; Yan, Si-Qi; Zhang, Kai-Long; Wu, Si-Cong; Sima, Yang-Hu; Zhang, Ke-Qin; He, Yao; Xu, Shi-Qing
Abstract: Silicon nanoparticles (SiNPs) have attractive potential applications in biological and medical fields, and yet their impact on animals is still controversial, and there have been no reports of their effects on hematopoiesis. In this study, the effects of SiNPs on hemocytes and hematopoiesis were investigated by administering SiNPs via a vascular injection into an invertebrate model, the silkworm. Our results show that the ability of SiNPs to enter different types of circulating hemocytes and their impact on those hemocytes differed significantly. Rapid accumulation of SiNPs was observed in granulocytes, oenocytoids, and spherulocytes, which have immune functions in the circulating hemolymph, whereas SiNPs did not easily enter prohemocytes, which can differentiate into granulocytes, oenocytoids, and spherulocytes and replenish them. The SiNPs that entered the hemocytes initiated autophagy and apoptosis via the lysosomal/mitochondrial pathway. High-dose SiNPs weakly stimulated lysosomal activity in hematopoietic organs, but did not lead to a significant increase in reactive oxygen species or severe autophagy or apoptosis in the organ tissues. We suggest that the damage caused by high-dose SiNPs to hematopoiesis is self-healing, because few SiNPs entered the hematopoietic stem cells in the circulating hemolymph, so the damage to the hematopoietic tissues was limited. Highlights: SiNPs selectively entered circulating hemocytes and induced apoptosis. The hematopoiesis of hematopoietic organs reduced by SiNPs. Hematopoietic organs secreted hemocytes return to normal after Self-healing.